Terapival vid behandling av lunginflammation hos kalv - Holmquist, Jenny (2006)
The purpose of this study was to investigate the kind of treatment strategies used by Swedish Veterinarians with cattle practice when treating calves with symptoms of pneumonia. A questionnaire, consisting of seven questions, was sent to one hundred veterinarians who have had practice with cattle and are employed by the Swedish Board of Agriculture. The survey was answered by a total of 73% of the Veterinarians. Of the respondents, 73 % use Penicillins as their first choice of drug for treating calves with symptoms of pneumonia, and as their second choice 64 % use Tetracycline. Supplementary treatment such as NSAID (non-steroidal anti-inflammatory drugs) and/or SAID (steroid anti-inflammatory drugs) are used by 97.5 % of the respondents. Both NSAID and SAID are used, from case to case by 48 % of the respondents. SAID was used by it self by 2.5 % of those who answered the survey and 47 % used exclusivley NSAID. Many of the respondents (74 %) believe their treatment results are good and 23 % think their results are very good. Not one of the respondents felt that their treatment lacked a positive effect. 85% of the Veterinarians believed that possible therapy failure can be a result of a late start in therapy treatment. A literary study about the subject with focus on treatment of pneumonia has also been conducted. Recommendations for antibiotic treatment of calves with pneumonia differ widely in literature, most probably reflecting the differences of the bacterias resistance pattern between countries. It was found that Penicillin should be the drug of choice in Sweden for treating calves suffering from pneumonia due to the low resistance among bacterias. Comparative studies have shown that NSAID treatment is superior to SAID treatment regarding the anti-inflammatory effect. The choice of NSAID substance is subordinate.